A nickel-iron composite catalyst, a preparation method and application thereof

CN117966208BActive Publication Date: 2026-10-20JIANGSU UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410109079.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-25
Publication Date
2026-10-20
Estimated Expiration
2044-01-25

AI Technical Summary

Technical Problem

镍铁元素因储量丰富、性能突出受到广泛关注,不同类型镍铁基催化材料具有OER催化性能,但多存在金属载量高、质量活性低,其性能仍有待提高

Benefits of technology

[0021]有益效果:与现有技术相比,本发明具有如下显著优点:(1)该催化剂在镍铁中引入2,2'-联吡啶和碳纳米管,利用2,2'-联吡啶配位能力强的特点,调节镍铁双金属的配位环境并优化它们之间的协同作用,获得了优异的OER电催化性能,在高导电性碳纳米管的协同作用下进一步加快了电化学反应动力学过程,表现出高效OER催化性能;(2)当2,2'-联吡啶与Ni-Fe二金属单元以摩尔比1:2的比例添加得到性能最优样——NiFe(2,2'-bpy)2@CNT,其在1M KOH中的析氧过电位η10仅为240mV,优于或接近大多数在较为复杂条件下合成的镍铁基催化剂材料;(3)该制备方法简单、原料易得、在常温常压下进行,便于扩大生产,以解决当前工业电催化剂成本高昂的问题;(4)该方法所用金属载量低,镍铁质量分数均低于1.5%,为构建其他低金属载量的非贵金属、贵金属催化剂提供了新的方法参考。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117966208B_ABST
    Figure CN117966208B_ABST
Patent Text Reader

Abstract

The application discloses a nickel-iron composite catalyst and a preparation method and application thereof. n @CNT, wherein n=1-3; the preparation method comprises the following steps: dissolving a soluble nickel salt and an iron salt in an ethanol solution to obtain solution 1; dissolving 2,2'-bipyridine in an ethanol solution to obtain solution 2; dispersing carbon nanotubes in an ethanol solution to obtain solution 3; adding solution 1 and solution 2 into solution 3; and removing a solvent from the mixed solution to obtain a black solid, which is the catalyst. The catalyst introduces 2,2'-bipyridine and carbon nanotubes into nickel-iron, utilizes the strong coordination ability of 2,2'-bipyridine, adjusts the coordination environment of the nickel-iron bimetal and optimizes the synergistic effect between them, and thus excellent OER electrocatalytic performance is obtained; and the high-conductivity carbon nanotubes further accelerate the electrochemical reaction kinetics process, and thus high-efficiency OER catalytic performance is exhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a catalyst, its preparation method and application, and particularly to a nickel-iron composite catalyst, its preparation method and application. Background Technology

[0002] Electrolysis of water is a promising method for obtaining green hydrogen energy, but the slow kinetics of the oxygen evolution reaction (OER) at the anolyte severely affect hydrogen production efficiency. Noble metal electrocatalysts such as iridium dioxide and ruthenium dioxide can effectively catalyze the OER reaction, but their scarcity and high cost hinder large-scale production applications. Therefore, designing non-noble metal OER electrocatalysts holds great promise. Currently, significant progress has been made in the research of non-noble metal OER catalysis. Nickel-iron elements have attracted widespread attention due to their abundant reserves and outstanding performance. Different types of nickel-iron-based catalytic materials possess OER catalytic performance, but many suffer from high metal loading and low mass activity, and their performance still needs improvement. Summary of the Invention

[0003] Objectives of the Invention: The first objective of this invention is to provide a nickel-iron composite catalyst that improves the catalytic performance of nickel-iron oxygen evolution catalysts; the second objective of this invention is to provide a method for preparing the catalyst; and the third objective of this invention is to provide the application of the catalyst in the oxygen evolution reaction of water electrolysis.

[0004] Technical solution: The nickel-iron composite catalyst of the present invention has the chemical formula NiFe(2,2'-bpy). n @CNT, where n = 1 to 3, 2,2'-bpy is 2,2'-bipyridine, and CNT is carbon nanotube.

[0005] The coordination modes of Ni, Fe and 2,2'-bipyridine are as follows:

[0006]

[0007] NiFe(2,2'-bpy) n In @CNTs, 2,2'-bipyridine, as a bidentate chelating organic ligand, can coordinate with Ni and Fe to different degrees of saturation, while the uncoordinated spatial orientation serves as the catalytic active site for the oxygen evolution reaction. The Ni-Fe metallic phase coordinated with 2,2'-bipyridine binds to carbon nanotubes in the form of nanoparticles.

[0008] Preferably, the NiFe(2,2'-bpy) n In @CNT, n is 1.5 to 2.5.

[0009] Preferably, the NiFe(2,2'-bpy) n In @CNT, the Ni-Fe metallic phase consists of nanoparticles ranging from 10 to 50 nm.

[0010] Preferably, the NiFe(2,2'-bpy) n The molar ratio of Ni-Fe to carbon nanotubes in @CNT is 1:320-350.

[0011] The preparation method of the nickel-iron composite catalyst of the present invention includes the following steps:

[0012] (1) Dissolve soluble nickel salt and ferric nitrate in ethanol solution to obtain a transparent mixed solution 1;

[0013] (2) Dissolve 2,2'-bipyridine in an ethanol solution to obtain a clear solution 2;

[0014] (3) Carbon nanotubes were dispersed in an ethanol solution to obtain a black suspension solution 3;

[0015] (4) Add solutions 1 and 2 to solution 3, remove the solvent from the mixture, and obtain a black solid nickel-iron-carbon nanotube composite catalyst with 2,2'-bipyridine coordination.

[0016] Preferably, in step (4), the solvent removal is achieved by allowing the solvent to evaporate naturally.

[0017] Preferably, the soluble nickel salt is nickel nitrate, nickel nitrate hexahydrate, nickel sulfate, or nickel chloride. Preferably, the soluble iron salt is ferric nitrate, ferric nitrate nonhydrate, ferric sulfate, or ferric chloride.

[0018] The application of the nickel-iron composite catalyst described in this invention in the oxygen evolution reaction of water electrolysis.

[0019] Preferably, the electrolyzed water is alkaline.

[0020] Mechanism of Invention: Ligand catalysis is an effective means to improve catalyst activity. By designing the ligand structure, the coordination environment of the metal active center can be changed, and the active sites of the catalyst can be controlled, thereby improving its catalytic performance. 2,2'-Bipyridine is a multidentate nitrogen-containing chelate ligand, in which the nitrogen atom can provide a lone pair of electrons to coordinate with the metal active center, exhibiting strong coordination ability. This invention uses 2,2'-bipyridine as an organic ligand to construct a 2,2'-bipyridine-coordinated nickel-iron carbon nanotube composite catalyst with nickel-iron metal. The strong coordination effect of 2,2'-bipyridine is utilized to regulate the coordination environment of the nickel-iron bimetal and improve its catalytic performance. In NiFe(2,2'-bpyridine) nIn the @CNT catalyst, 2,2'-bipyridine acts as a bidentate chelating organic ligand, enabling coordination with Ni and Fe at different saturation levels (n). The active catalytic sites in the nickel-iron octahedral coordination field gradually decrease with increasing n, significantly impacting catalytic performance. When 2,2'-bipyridine undergoes unsaturated coordination with nickel-iron, the unique coordination configuration optimizes and improves the charge density around the nickel-iron metal, thereby improving the desorption Gibbs free energy (ΔG) between the metal sites and the active intermediates (*OH, *O, *OOH, * representing the catalyst active site). Ultimately, under the synergistic effect of highly conductive carbon nanotubes, this significantly improves the electrochemical reaction kinetics and enhances OER catalytic performance. This synthetic method is green, simple, and pollution-free. The catalyst exhibits superior catalytic performance compared to pure nickel-iron carbon nanotube composite catalysts. The introduction of the organic 2,2'-bipyridine ligand provides ample space for subsequent functionalization design of the catalyst.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The catalyst introduces 2,2'-bipyridine and carbon nanotubes into nickel-iron bimetallic materials. By utilizing the strong coordination ability of 2,2'-bipyridine, the coordination environment of the nickel-iron bimetallic materials is adjusted and the synergistic effect between them is optimized, resulting in excellent OER electrocatalytic performance. Under the synergistic effect of highly conductive carbon nanotubes, the electrochemical reaction kinetics process is further accelerated, showing highly efficient OER catalytic performance; (2) When 2,2'-bipyridine and Ni-Fe bimetallic units are added in a molar ratio of 1:2, the optimal performance sample is obtained - NiFe(2,2'-bpy)2@CNT, whose oxygen evolution overpotential η in 1M KOH is the highest. 10 The value is only 240mV, which is better than or close to most nickel-iron based catalyst materials synthesized under more complex conditions; (3) The preparation method is simple, the raw materials are readily available, and it is carried out at room temperature and pressure, which facilitates the expansion of production to solve the problem of high cost of current industrial electrocatalysts; (4) The metal loading used in this method is low, and the mass fraction of nickel-iron is less than 1.5%, which provides a new method reference for constructing other non-precious metal and precious metal catalysts with low metal loading. Attached Figure Description

[0022] Figure 1 The image shows a scanning electron microscope (SEM) image of the catalyst NiFe(2,2'-bpy)2@CNT prepared according to Example 2.

[0023] Figure 2 Transmission electron microscopy (TEM) image of the catalytic material NiFe(2,2'-bpy)2@CNT prepared according to Example 2;

[0024] Figure 3 The image shows the X-ray diffraction (XRD) pattern of the catalytic material prepared in Example 2.

[0025] Figure 4 Infrared spectra of the catalytic materials prepared in Example 2 and Comparative Example 1;

[0026] Figure 5 The OER polarization curves of the catalytic materials prepared in Examples 1-3 and Comparative Examples 1-2, as well as carbon nanotubes (CTN) and commercially available IrO2, in 1.0 M KOH solution are shown. Detailed Implementation

[0027] The technical solution of the present invention will be further described below with reference to the embodiments.

[0028] Example 1

[0029] The nickel-iron composite catalyst of the present invention is prepared by means of the following steps:

[0030] (1) Dissolve 0.58 g (2 mmol) nickel nitrate hexahydrate and 0.808 g (2 mmol) ferric nitrate nonahydrate in 20 mL of ethanol solution by ultrasonication to obtain a transparent mixed solution 1;

[0031] (2) 0.31 g (2 mmol) of 2,2'-bipyridine was ultrasonically dispersed and dissolved in 20 mL of ethanol solution to obtain a transparent solution 2;

[0032] (3) 40 mg (3.3 mmol) of carbon nanotubes were ultrasonically dispersed in 4.8 mL of ethanol solution to obtain black solution 3;

[0033] (4) Add 100 μL of solution 1 and 100 μL of solution 2 to solution 3, sonicate for 10 minutes to mix them evenly, and then place the mixed solution under room temperature and natural ventilation conditions. After the solvent evaporates, the black solid sample NiFe(2,2'-bpy)@CNT is obtained.

[0034] Based on the experimental reaction, the calculated mass percentage of nickel-iron metal in the product was 1.5%, and the mass fraction of 2,2'-bipyridine was 4%.

[0035] Example 2

[0036] The nickel-iron composite catalyst of the present invention is prepared by means of the following steps:

[0037] (1) Dissolve 0.58 g (2 mmol) nickel nitrate hexahydrate and 0.808 g (2 mmol) ferric nitrate nonahydrate in 20 mL of ethanol solution by ultrasonication to obtain a transparent mixed solution 1;

[0038] (2) 0.31 g (2 mmol) of 2,2'-bipyridine was ultrasonically dispersed and dissolved in 20 mL of ethanol solution to obtain a transparent solution 2;

[0039] (3) 40 mg (3.3 mmol) of carbon nanotubes were ultrasonically dispersed in 4.8 mL of ethanol solution to obtain black solution 3;

[0040] (4) Add 100 μL of solution 1 and 200 μL of solution 2 to solution 3, sonicate for 10 minutes to mix them evenly, and then place the mixed solution under room temperature and natural ventilation conditions. After the solvent evaporates, the black solid sample NiFe(2,2'-bpy)2@CNT is obtained.

[0041] Based on the experimental reaction, the calculated mass percentage of nickel-iron metal in the product was 1.5%, and the mass fraction of 2,2'-bipyridine was 8%.

[0042] Example 3

[0043] The nickel-iron composite catalyst of the present invention is prepared by means of the following steps:

[0044] (1) Dissolve 0.58 g (2 mmol) nickel nitrate hexahydrate and 0.808 g (2 mmol) ferric nitrate nonahydrate in 20 mL of ethanol solution by ultrasonication to obtain a transparent mixed solution 1;

[0045] (2) 0.31 g (2 mmol) of 2,2'-bipyridine was ultrasonically dispersed and dissolved in 20 mL of ethanol solution to obtain a transparent solution 2;

[0046] (3) 40 mg (3.3 mmol) of carbon nanotubes were ultrasonically dispersed in 4.8 mL of ethanol solution to obtain black solution 3;

[0047] (4) Add 100 μL of solution 1 and 300 μL of solution 2 to solution 3, sonicate for 10 minutes to mix them evenly, and then place the mixed solution under room temperature and natural ventilation conditions. After the solvent evaporates, the black solid sample NiFe(2,2'-bpy)3@CNT is obtained.

[0048] Based on the experimental reaction, the calculated mass percentage of nickel-iron metal in the product was 1.5%, and the mass fraction of 2,2'-bipyridine was 12%.

[0049] Comparative Example 1

[0050] (1) Dissolve 0.58 g (2 mmol) nickel nitrate hexahydrate and 0.808 g (2 mmol) ferric nitrate nonahydrate in 20 mL of ethanol solution by ultrasonication to obtain a transparent mixed solution 1;

[0051] (2) 0.31 g (2 mmol) of 2,2'-bipyridine was ultrasonically dispersed and dissolved in 20 mL of ethanol solution to obtain a transparent solution 2;

[0052] (3) 40 mg (3.3 mmol) of carbon nanotubes were ultrasonically dispersed in 4.8 mL of ethanol solution to obtain black solution 3;

[0053] (4) Add 100 μL of solution 1 and 0 μL of solution 2 to solution 3, sonicate for 10 minutes to mix them evenly, and then place the mixed solution under room temperature and natural ventilation conditions. After the solvent evaporates, the black solid sample NiFe@CNT is obtained.

[0054] Based on the experimental reaction, the calculated mass percentage of nickel-iron metal in the product was 1.5%, and the mass fraction of 2,2'-bipyridine was 0%.

[0055] Comparative Example 2

[0056] (1) Dissolve 0.58 g (2 mmol) nickel nitrate hexahydrate and 0.808 g (2 mmol) ferric nitrate nonahydrate in 20 mL of ethanol solution by ultrasonication to obtain a transparent mixed solution 1;

[0057] (2) 0.31 g (2 mmol) of 2,2'-bipyridine was ultrasonically dispersed and dissolved in 20 mL of ethanol solution to obtain a transparent solution 2;

[0058] (3) 40 mg (3.3 mmol) of carbon nanotubes were ultrasonically dispersed in 4.8 mL of ethanol solution to obtain black solution 3;

[0059] (4) Add 100 μL of solution 1 and 500 μL of solution 2 to solution 3, sonicate for 10 minutes to mix them evenly, and then place the mixed solution under room temperature and natural ventilation conditions. After the solvent evaporates, the black solid sample NiFe(2,2'-bpy)5@CNT is obtained.

[0060] Based on the experimental reaction, the calculated mass percentage of nickel-iron metal in the product was 1.5%, and the mass fraction of 2,2'-bipyridine was 20%.

[0061] Structural characterization

[0062] The catalyst prepared in Example 2 was structurally characterized, and the results are as follows: Figure 1 and 2 As shown, Figure 1 This is a scanning electron microscope (SEM) image. Figure 2 This is a transmission electron microscope (TEM) image.

[0063] Depend on Figure 1 As can be seen, compared to pure carbon nanotubes, the nickel-iron phase of the catalyst obtained in Example 2 is attached to the carbon nanotubes as an amorphous nanocrystalline phase. Due to the low loading, no large nickel-iron crystalline phase was observed to precipitate; it only adhered around the carbon nanotubes at a size similar to or close to that of the carbon nanotubes.

[0064] Depend on Figure 2 It can be seen that nickel-iron nanocrystalline phases are attached to the surface of carbon nanotubes.

[0065] The catalyst prepared in Example 2 was characterized using X-ray diffraction (XRD). The results are as follows: Figure 3 As shown.

[0066] Depend on Figure 3 The catalyst exhibited distinct broad diffraction peaks at approximately 2θ = 25° and 43°, which are characteristic peaks of the graphite phase of CNTs (JCPDS No. 01-0646). No detectable diffraction peaks were observed in the Ni / Fe(2,2'-bpy)2 supported material, which can be attributed to the low loading of the coordination phase leading to interference and coverage of the diffraction signal by the carbon material.

[0067] The catalytic materials prepared in Example 2 and Comparative Example 1 were characterized using infrared spectroscopy, and the results are as follows: Figure 4 As shown.

[0068] Depend on Figure 4 It can be seen that the catalyst material NiFe(2,2-bpy)2@CNT obtained in Example 2 has a performance at 1600 cm⁻¹ -1 1000-1200cm -1 and 750-800cm -1 All exhibited characteristic absorptions of the bipyridine organic group, corresponding to the stretching vibration of pyridine C=N, the vibration of the aromatic ring, and the rocking vibration of CH, respectively. Simultaneously, the corresponding spectral peaks showed a certain degree of blue shift (wavenumber shift towards higher wavenumbers), proving that 2,2'-bipyridine coordinated with metal ions in the NiFe(2,2-bpy)2@CNT composite material.

[0069] Performance testing

[0070] The catalytic performance of the catalysts prepared in Examples 1-3 and Comparative Examples 1-2, carbon nanotubes (CTN), and commercially available IrO2 in catalytic water splitting and oxygen evolution was tested.

[0071] Test method: The oxygen evolution performance of the catalyst material was tested in a standard three-electrode system, in which the glassy carbon electrode (φ: 5mm) supporting the catalyst material was used as the working electrode, the graphite carbon rod was used as the counter electrode, and the HgO / Hg electrode was used as the reference electrode.

[0072] Test results are as follows Figure 5 As shown.

[0073] Depend on Figure 5It can be seen that, in Examples 1-3, the catalytic performance of the prepared catalysts first increased and then decreased with increasing amounts of 2,2'-bipyridine. When the coordination saturation is low, uncoordinated sites are occupied by solvent molecules or anions. These sites allow the reaction between the Ni / Fe center and the OH- anion to form Ni / Fe-2,2'-bpy-based hydroxides with high catalytic activity for OER. However, as the coordination of 2,2'-bpy increases, a significant steric hindrance effect around the Ni / Fe center is also caused, which in turn inhibits the hydroxylation process and reduces the catalytic activity. The oxygen evolution overpotential η of the catalysts in Examples 1-3 in 1M KOH is... 10 The values ​​were 250mV, 240mV, and 260mV, respectively. When Ni-Fe dimetallic units and 2,2'-bipyridine were added at a molar ratio of 1:2, the optimal-performance sample—NiFe(2,2'-bpy)2@CNT—was obtained, and its oxygen evolution overpotential η in 1M KOH was [value missing]. 10 With a value of only 240mV, it is superior to or close to most nickel-iron-based catalyst materials synthesized under more complex conditions.

[0074] The oxygen evolution overpotential η of the catalysts prepared in Comparative Examples 1 and 2 in 1M KOH 10 The values ​​were 270 mV and 380 mV, respectively. The catalytic effect of Comparative Example 1 was not as good as that of the catalysts prepared in Examples 1-3. This is because 2,2'-bipyridine was not added to the comparative example, and the catalytic coordination optimization effect of 2,2'-bipyridine on the active metal site was lacking. In Comparative Example 2, an excess of 2,2'-bipyridine was added, and the hydroxylation process was inhibited by the fully coordinated 2,2'-bpy-Ni / Fe, resulting in a relatively lower OER performance.

Claims

1. A nickel-iron composite catalyst, characterized in that, The chemical formula is NiFe(2,2'-bpy). n @CNT, where n=1~3, 2,2'-bpy is 2,2'-bipyridine, and CNT is carbon nanotube; the NiFe(2,2'-bpy) n The molar ratio of Ni-Fe to carbon nanotubes in @CNT is 1:320~350; Among them, 2,2'-bipyridine, as a bidentate chelating organic ligand, can coordinate with Ni and Fe to different degrees of saturation, and the uncoordinated spatial orientation serves as the catalytic active site for the oxygen evolution reaction; the Ni-Fe metal phase coordinated by 2,2'-bipyridine interacts with carbon nanotubes in the form of nanoparticles; the nickel-iron phase is an amorphous nanocrystalline phase.

2. The nickel-iron composite catalyst according to claim 1, characterized in that, The NiFe(2,2'-bpy) n In @CNT, n is 1.5~2.

5.

3. The nickel-iron composite catalyst according to claim 1, characterized in that, The NiFe(2,2'-bpy) n In @CNT, the Ni-Fe metallic phase consists of nanoparticles of 10~50 nm.

4. A method for preparing the nickel-iron composite catalyst according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Dissolve soluble nickel and iron salts in ethanol solution to obtain a transparent mixed solution 1; (2) Dissolve 2,2'-bipyridine in an ethanol solution to obtain a clear solution 2; (3) Carbon nanotubes were dispersed in an ethanol solution to obtain a black suspension 3; (4) Add solution 1 and solution 2 to solution 3, remove the solvent from the mixture, and obtain a black solid nickel-iron-carbon nanotube composite catalyst with 2,2'-bipyridine coordination.

5. The method for preparing the nickel-iron composite catalyst according to claim 4, characterized in that, In step (4), the solvent removal is achieved by allowing the solvent to evaporate naturally.

6. The method for preparing the nickel-iron composite catalyst according to claim 4, characterized in that, The soluble nickel salt is nickel nitrate, nickel nitrate hexahydrate, nickel sulfate, or nickel chloride.

7. The method for preparing the nickel-iron composite catalyst according to claim 4, characterized in that, The soluble iron salt is ferric nitrate, ferric nitrate nonhydrate, ferric sulfate, or ferric chloride.

8. The application of the nickel-iron composite catalyst according to any one of claims 1 to 3 in the oxygen evolution reaction of water electrolysis.

9. The application according to claim 8, characterized in that, The electrolyzed water is alkaline.

Citation Information

Patent Citations

  • Oxalate-based ferronickel MOF doped carbon nanotube catalytic material, preparation method and application

    CN116905041A